2015
DOI: 10.1179/1743294414y.0000000422
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between structure and properties of annealed electroless Ni–W–P coatings

Abstract: Ni-W-P coatings with different structures were prepared by electroless deposition. The correlation between the coating structure before and after annealing with hardness and corrosion resistance has been examined by microhardness measurement, potentiodynamic polarisation and corrosion weight loss tests, and by quantitative X-ray diffraction technology and scanning electron microscopy observation of the corrosion morphology. The results indicate that incorporation of tungsten (4-5 wt-%) in Ni-P deposits does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Better thermal stability is obtained for baths containing 20g/L sodium tungstate. A correlation between the structure of electroless deposited Ni-P-W coating with the hardness and corrosion behavior has been established by Liu et al [37]. It is revealed that with heat treatment of the coatings at a temperature of 300°C or below, the increase in hardness is mainly due to the crystallization of nickel from the amorphous phase and not to Ni 3 P. Peak hardness is obtained for a heat treatment temperature of 400 or 500°C, which can be mainly attributed to the precipitation of Ni 3 P phase.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Better thermal stability is obtained for baths containing 20g/L sodium tungstate. A correlation between the structure of electroless deposited Ni-P-W coating with the hardness and corrosion behavior has been established by Liu et al [37]. It is revealed that with heat treatment of the coatings at a temperature of 300°C or below, the increase in hardness is mainly due to the crystallization of nickel from the amorphous phase and not to Ni 3 P. Peak hardness is obtained for a heat treatment temperature of 400 or 500°C, which can be mainly attributed to the precipitation of Ni 3 P phase.…”
Section: Introductionmentioning
confidence: 91%
“…From an extensive review of literature, it seems that the research concerning electroless Ni-P-W coating is mainly directed towards the investigation of surface morphology, microstructure, corrosion resistance, microhardness, wear resistance and friction behavior. The effect of different heat and surface treatments on the same has also been studied, while the tribological behavior has been investigated mostly under dry sliding condition [31][32][33][34][35][36][37][38][39][40][41][42][43]. Investigation of tribological behavior of EN coatings under lubricated condition is seen to be mostly concentrated around Ni-P binary alloy coatings and its composite variants [13,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the third element depends on the application for which the coating is required. Inclusion of Mo or W improves thermal stability of EN coatings, tribological characteristics, and corrosion resistance [14][15][16][17][18]. Inclusion of Cu also leads to an improvement in corrosion resistance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Akımsız Ni-P kaplamaların sertliği tungsten ilavesi ile arttırılabildiği önceki çalışmalarda bildirilmiştir (H. Liu et al, 2015). Ayrıca çoğu yazar tarafından Ni-W-P kaplamanın Ni-P'den daha iyi bir korozyon direncine sahip olduğu bildirilmektedir.…”
Section: Introductionunclassified